Nobel Prize in Economics: retrospective analysis and prediction of laureates - Totska, Olesia Leontiivna; Тоцька, Олеся Леонтіївна (Fundação Pedro Leopoldo, 2023)
The purpose of the article is to analyze retrospective data on the laureates of the Sveriges Riksbank Prize in Economic Sciences in Memory of Alfred Nobel for the years 1969-2022 and to try to predict three parameters of 2023: the number of scientists who will receive the award; the part of the world in which the place of work of the laureate(s) is located; age of laureate / average age of laureates. During the years 1969–2022, the prize was awarded 54 times, and 92 people became its laureates. 74 awardees are affiliated with North America. The age of most scientists at the time of awarding was from 61 to 70 years. According to the obtained forecast trend models, in 2023 the laureates of the prize will be 3 people, representatives of higher education institutions from North America, whose average age will be in the range of 61–70 years.

Метою статті є аналіз ретроспективних даних щодо лауреатів Премії Шведського центрального банку з економічних наук пам'яті Альфреда Нобеля за 1969-2022 роки та спроба спрогнозувати три параметри 2023 року: кількість вчених, які отримають нагороду; частину світу, в якій знаходиться місце праці лауреата(ів); вік лауреата / середній вік лауреатів. Протягом 1969–2022 років премію вручали 54 рази, її лауреатами стали 92 особи. Афіліація 74 лауреатів пов’язана зі Північною Америкою. Вік більшості науковців на час нагородження був від 61 до 70 років. Згідно отриманих прогнозних трендових моделей, у 2023 році лауреатами премії буде 3 особи, представники закладів вищої освіти з Північної Америки, середній вік яких перебуватиме в діапазоні 61–70 років.
Нобелівська премія з економіки: ретороспективний аналіз і прогнозування лауреатів
Keywords: Nobel Prize; laureates in economics; analysis; prognostication; retrospective data; Нобелівська премія; лауреати з економіки; аналіз; прогнозування; ретроспективні дані